Flying into Frictioned Futures: Development of Canada’s Northernmost Runways - Schmid, Katrin (Anthropologica)

(untitled) (University of Victoria, 2025)
In Nunavut, Canada’s largest, youngest, and northernmost territory, gravel, asphalt, and concrete determine much of daily life. Airport runways’ materialities dictate the types of aircraft that can land in each of the 25 fly-in communities and with them the cargo-carrying capacity, passenger mobility, and frequency of intercommunity connections. The last jet capable of landing on gravel was recently phased out of commercial service in Nunavut, a move that further limits access to communities and works counter to desires voiced by residents to increase jet access. Temporality, an immaterial concept, becomes intimately articulated through the physical realities of transport infrastructure in Nunavut. I examine the interplay of residents’ imagined futures for their communities and the on-the-ground reality of developing, operating, and maintaining gravel and paved runways in Nunavut as points of friction, following Anna Tsing. I argue that the divergent development of communities can be partially attributed to the accessibility of transport infrastructure in each location. In conclusion, I question the idea of infrastructure as a promise of a “future perfect” (Hetherington 2016) and attempt to refocus the processes of Nunavut’s transport infrastructure development onto Nunavummi-centred solutions.